Automated Awareness Safety System (AwAS) for Red Light Running in Malaysia: An Analysis of Four-year Data on Its Effectiveness - H. Mohamed Jamil; A. Shabadin; M. K. A. Ibrahim (Journal of the Society of Automotive Engineers Malaysia, 2022)
This paper discusses the trend of red light running (RLR) due to the implementation of the Automated Awareness Safety System (AwAS): Red Light Camera (RLC) in Malaysia. Since 2012, the government has installed the then Automated Enforcement System (AES) cameras at selected locations as a measure to reduce red light running. Its installation is controversial as to whether it improves safety or merely acted as a revenue generator to Malaysia. Four accident-prone signalized intersections were chosen as the study location. Four enumerators, together with four video cameras were placed unobtrusively to collect data in terms of traffic volume and number of violations for pre and post-installation (six months, one year, two years, and four years) considering factors influencing red light violations (location type, vehicle type, time and type-of-day). Results showed an overall reduction in violation rate two years after installation with 2.61% compared to before installation (4.29%) and an increase again four years after with 3.82%. Motorcycles are the highest RLR violator whereas cars and other types of vehicles recorded almost similar violation rates. Based on location type, Perak had higher violation rates before installation (5.19%) compared to Kuala Lumpur (3.71%). However, the tables have turned with Kuala Lumpur having the higher violation rates with 2.49% two years after and 4.55% after four years; whereas Perak with 1.57% and 2.64% respectively. The violation rate trend for both times and type-of-day were also similar. Findings in the study revealed that the implementation of AwAS was undoubtedly timely and was found to be beneficial in Malaysia.